Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s40463-018-0275-x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of in-office flexible fiber-optic biopsies for laryngopharyngeal lesions

Abstract: BackgroundOperative endoscopy and flexible fiber-optic in-office tissue biopsy are common techniques to assess suspicious laryngopharyngeal lesions.MethodsThe primary outcome was the delay to the initiation of treatment. Secondary outcomes were delay to biopsy, histopathological diagnosis, and assessment at a multidisciplinary oncology clinic. A retrospective analysis was performed to assess the relative delays between these approaches to biopsy of laryngopharyngeal lesions.ResultsThere were 114 patients in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…As seen in Table 5, in contrast, Lee et al [25] did not find any significant difference for timeto-treatment, despite observing a reduced time-to-diagnosis by 15.5 days with IOB. They account for the loss of this initial advantage of IOB due to a combination of system factors and referral bias.…”
Section: Waiting Timesmentioning
confidence: 70%
“…As seen in Table 5, in contrast, Lee et al [25] did not find any significant difference for timeto-treatment, despite observing a reduced time-to-diagnosis by 15.5 days with IOB. They account for the loss of this initial advantage of IOB due to a combination of system factors and referral bias.…”
Section: Waiting Timesmentioning
confidence: 70%
“…Lee et al . 31 performed a retrospective study on 114 patients, of which 44 underwent out-patient biopsy. They looked at time to diagnosis and treatment between the two groups.…”
Section: Resultsmentioning
confidence: 99%
“…Diagnosis using in-office endoscopic biopsy has been shown to be more time efficient, possibly leading to a better patient outcome. Lee et al 31 performed a retrospective study on 114 patients, of which 44 underwent out-patient biopsy. They looked at time to diagnosis and treatment between the two groups.…”
Section: Time For Diagnosismentioning
confidence: 99%
“…FEB, however, is a less invasive alternative. Advantages of FEB include the elimination of GA, 5 negation of patients' anatomical limitations, 14 shortened time to diagnosis, 8,15 and reduction in health care costs. 2,7 Previous studies have demonstrated that FEB is safe, 1−6,9−12 feasible, 2,3,6,7 and tolerated by patients.…”
Section: Introductionmentioning
confidence: 99%